2020
DOI: 10.1111/add.15355
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis on the association between solitary drinking and alcohol problems in adults

Abstract: Background and aims Solitary drinking in adolescents and young adults is associated with greater risk for alcohol problems, but it is unclear whether this association exists in older demographics. The current paper is the first meta‐analysis and systematic review to determine whether adult solitary drinking is associated with greater risk for alcohol problems. Methods PsychINFO, PubMed, and Google Scholar were searched following a pre‐registered PROSPERO protocol (CRD42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 88 publications
(338 reference statements)
4
26
1
1
Order By: Relevance
“…However, an additive effect of this separate phenomenon is a more likely explanation, but this conjecture needs to be confirmed in longitudinal settings. Approximately 10% of all home alone occasions were intoxication occasions by 2016, and their share of all intoxication occasions increased from 4% in 2000 to 14% in 2016; even if most solitary drinking was light drinking, a part can be connected to heavy drinking, marginalization and health problems [28] or can reflect emerging symptoms of use disorder [29], and can (when frequent) contribute to chronically high alcohol exposure. Hence, these occasions contribute to alcohol problems and should be considered in prevention work.…”
Section: Discussionmentioning
confidence: 99%
“…However, an additive effect of this separate phenomenon is a more likely explanation, but this conjecture needs to be confirmed in longitudinal settings. Approximately 10% of all home alone occasions were intoxication occasions by 2016, and their share of all intoxication occasions increased from 4% in 2000 to 14% in 2016; even if most solitary drinking was light drinking, a part can be connected to heavy drinking, marginalization and health problems [28] or can reflect emerging symptoms of use disorder [29], and can (when frequent) contribute to chronically high alcohol exposure. Hence, these occasions contribute to alcohol problems and should be considered in prevention work.…”
Section: Discussionmentioning
confidence: 99%
“…It will be important to test the hypothesized framework in older individuals, especially given the increasing prevalence of social isolation associated with aging (Luo, Hawkley, Waite, & Cacioppo, 2012). Standardizing the definition of solitary drinking to mean drinking while no one else is physically (or virtually) present would help to further clarify associations between solitary drinking and relevant variables, given that some researchers have defined solitary drinking as drinking with nondrinking other people or among noninteracting others (see Skrzynski & Creswell, 2020a, 2020b).…”
Section: Future Directionsmentioning
confidence: 99%
“…Future studies are needed to determine whether there are differential negative consequences across social and solitary settings. It is also noteworthy that the vast majority of studies in this area have been conducted on adolescents and young adults (but see Skrzynski & Creswell, 2020b, for a meta-analysis on the association between solitary drinking and alcohol problems in adults). It will be important to test the hypothesized framework in older individuals, especially given the increasing prevalence of social isolation associated with aging (Luo, Hawkley, Waite, & Cacioppo, 2012).…”
Section: Future Directionsmentioning
confidence: 99%
“…Further, we recruited individuals who reported solitary drinking, but future studies might consider additional eligibility criteria including heavy drinking status and scoring highly on trait neuroticism, both of which might increase the likelihood of choosing to drink alone in the context of a negative mood induction. This study focused on young adults, and future studies are indicated to explore mechanisms for solitary drinking among older individuals (see [ 50 ]). Finally, it is important to note that individuals who volunteer to participate in laboratory alcohol studies may not be representative of all drinking individuals.…”
Section: Discussionmentioning
confidence: 99%